PEMANGGILAN TERHADAP SAKSI KORBAN DI PERSIDANGAN DALAM PERKARA TINDAK PIDANA PENYEBARAN VIDEO PORNO: Summoning Victim Witnesses In Court In The Case Of The Crime Of Distributing Pornographic Videos - Fadel Abdurrazzaq; Azmi Syahputra (AMICUS CURIAE, 2025)
The public prosecutor is authorized to summon the victim to appear at the hearing and the summons must be issued at least three days before the trial begins. However, based on the object of the researcher's case, at the first hearing the victim didn’t receive a summons. The victim was informed that the case had entered the trial process at the second hearing. The problem is whether the summoning of victim in the trial of the crime of spreading pornographic videos is in accordance with the Criminal Procedure Code and how the proposed formulation of criminal procedure law in the future in order to protect the interests of victims. The results is Public Prosecutor has contradicted Article 152 (2) and Article 146 (2) of the Criminal Procedure Code. This action shows that the existing trial unfair. Therefore, it’s necessary to reformulate the Criminal Procedure Code related to the deadline for summoning victim and synchronize the Criminal Procedure Code which is derived into internal prosecutor's regulations related to the mechanism for summoning victim and sanctions to Public Prosecutor about assessment of prosecutorial performance.